Hadith #3755 - Sunan Abi Dawud - Abdul Salam bin Harb bin Salm al-Mala'i عبد السلام بن حرب بن سلم النهدي الملائي; Abu Khalid al-Dalani أبو خالد الدالاني الأسدي; Hameed bin 'Abdur Rahman حميد بن عبد الرحمن الحميري; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب (Sunan Abi Dawud)
Safinah AbuAbdurRahman said that a man prepared food for Ali ibn AbuTalib who was his guest, and Fatimah said: I wish we had invited the Messenger of Allah (ﷺ) and he had eaten with us. They invited him, and when he came he put his hands on the side-ports of the door, but when he saw the figured curtain which had been put at the end of the house, he went away. So Fatimah said to Ali: Follow him and see what turned him back. I (Ali) followed him and asked: What turned you back, Messenger of All
Grade: Hasan

Hadith #4650 - Sunan Abi Dawud - Abdul Salam bin Harb bin Salm al-Mala'i عبد السلام بن حرب بن سلم النهدي الملائي; Abdur Rahman bin Muhammad al-Maharbi عبد الرحمن بن محمد بن زياد المحاربي; Abu Hurairah; Abu Khalid al-Dalani أبو خالد الدالاني الأسدي; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب (Sunan Abi Dawud)
I was sitting with someone in the mosque of Kufah while the people of Kufah were with him. Then Sa’id ibn Zayd ibn Amr ibn Nufayl came and he welcomed him, greeted him, and seated him near his foot on the throne. Then a man of the inhabitants of Kufah, called Qays ibn Alqamah, came. He received him and began to abuse him. Sa’id asked: Whom is this man abusing? He replied: He is abusing Ali. He said: Don’t I see that the companions of the Messenger of Allah (ﷺ) are being abused, but you n
Grade: Sahih